2002
DOI: 10.1038/sj.bjc.6600344
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose-escalating study of DaunoXome, liposomal daunorubicin, in metastatic breast cancer

Abstract: The aims of this phase I study were to establish the maximum tolerated dose, safety profile and activity of liposomal daunorubicin, DaunoXome (NeXstar Pharmaceuticals), in the treatment of metastatic breast cancer. DaunoXome was administered intravenously over 2 h in 21 day cycles and doses were increased from 80 to 100, 120 and 150 mg m 2 . Sixteen patients were enrolled. A total of 70 cycles of DaunoXome were administered. The maximum tolerated dose was 120 mg m 2 , the dose-limiting toxicity being prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Early clinical studies indicated that liposomal daunorubicin may have a more favorable cardiac safety profile than the conventional formulation [15][16][17]. However, evidence of cardiotoxicity has been observed at higher cumulative doses of liposomal daunorubicin (600-900 mg/m 2 ) [18,19].…”
Section: Liposomal Daunorubicinmentioning
confidence: 99%
See 2 more Smart Citations
“…Early clinical studies indicated that liposomal daunorubicin may have a more favorable cardiac safety profile than the conventional formulation [15][16][17]. However, evidence of cardiotoxicity has been observed at higher cumulative doses of liposomal daunorubicin (600-900 mg/m 2 ) [18,19].…”
Section: Liposomal Daunorubicinmentioning
confidence: 99%
“…O'Byrne and colleagues conducted a phase I dose-escalation study to determine the maximum tolerated dose, safety profile, and activity of liposomal daunorubicin in the treatment of metastatic breast cancer (MBC) [18]. Sixteen anthracycline-naïve patients received 2-hour infusions of liposomal daunorubicin given every 21 days.…”
Section: Liposomal Daunorubicinmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Daunorubicin has also been incorporated into liposomes for the formulation of liposomal anticancer chemotherapy drugs. DaunoXome ® (Gilead Sciences, Inc) is a commercial liposomal formulation of daunorubicin in which the drug is entrapped into small unilamellar vesicles (45 nm) composed of DSPC and cholesterol in 2:1 molar ratio.…”
Section: Clinical Studies Of Liposomal-based Anticancer Drugs: Daunormentioning
confidence: 99%
“…41 Sixteen anthracycline-naïve patients received a 2-hour infusion of liposomal daunorubicin at an initial dose of 80 mg/m 2 every 21 days, which was increased to 100 mg/m 2 , 120 mg/m 2 , 150 mg/m 2 , and 180 mg/m 2 thereafter. All patients had normal cardiac function at baseline, defined as LVEF Ͼ 50%.…”
Section: 42mentioning
confidence: 99%